No Association of Polymorphisms in the Serotonin Transporter Gene with Thermal Pain Sensation in Healthy Individuals. (4th December 2014) - Schaldemose, Ellen Lund; Horjales-Araujo, Emilia; Demontis, Ditte; Eørglum, Anders D; Svensson, Peter; Finnerup, Nanna Brix
Background: Recent studies have suggested an association between genotypes affecting the expression of the serotonin transporter and thermal pain perception and the thermal grill. The aim of this study was to investigate differences in thermal and mechanical pain perception and the thermal grill in two groups of healthy volunteers according to their genotype, associated with either high (n = 40) or low (n = 40) expression of the serotonin transporter and according to gender. Cold and warm detection and pain thresholds, pressure pain threshold and cold, warm and pain sensations to single or alternating stimuli with cold (20°C) and warm (40°C) temperatures (known as the thermal grill) were determined. In addition, intensity of ongoing pain and area and intensity of pinprick hyperalgesia in the secondary hyperalgesic area following topical application of capsaicin and vehicle control (ethanol) were determined. Results: No significant differences in detection and pain thresholds for cold and warm temperatures, presence of paradoxical heat sensation, pressure pain threshold and pain responses to suprathreshold thermal stimuli were observed. There was also no difference in capsaicin-evoked ongoing pain and secondary hyperalgesia between the two genotype groups (p >0.4), also when subdivided by gender (p >0.17). In addition, there were no significant differences in the perception of the thermal grill between the two genotypes (p >0.5), also when subdivided by gender. Conclusions: Genotypes associated with high or low expression of the serotonin transporter were not associated with thermal pain thresholds, pressure pain threshold, pain after capsaicin application or responses to the thermal grill. The present results do not support that the investigated genotypes play a major role in thermal pain perception among healthy individuals.